The Effectiveness of Reading Strategies Training to Teach Reading Comprehension - Nofita Yanti (Jurnal Inovasi Pembelajaran, 2019)
This study investigated the effect of reading strategies training technique on the students’ reading skill in literal and inferential comprehension. The training techniques were modified from the procedure developed by Brown and Palincsar (1984), which involved three concrete reading strategies: predicting, text mapping, and summarizing. To achieve the purpose of this study, the quasi experimental design was conducted with the experimental group was given reading strategies training technique and the control group was conventional technique. The subjects were two classes of office administration tenth grade students of SMKN 1 Sooko. The instrument of this study was test that used to compare the students achievement which used reading strategies training technique. The test for the post-test was constructed in multiple choices. In this study mid-test score is a covariate, it is used to know the students’ average score both experimental and control group before giving the treatment. The experimental data were subjected to descriptive statistics of mid-test score and post-test score, and both the analysis of covariance (ANCOVA) of post-test score in literal and inferential comprehension. Furthermore, the increase of the mean score of teaching reading comprehension by using strategies training technique is higher than the conventional technique group. It means that two groups both of experimental and control group differ significantly in literal and inferential comprehension.